Changes in children's and adolescents' dietary intake after the implementation of Chile's law of food labeling, advertising and sales in schools: a longitudinal study - Gabriela Fretes; Camila Corvalán; Marcela Reyes; Lindsey Smith Taillie; Christina D. Economos; Norbert L.W. Wilson; Sean B. Cash (BMC, 2023)
Abstract Background In June 2016, a comprehensive food policy was implemented in Chile that included front-of-package warning labels on key nutrients of concern (total sugars, added saturated fats, sodium, and calories), child-directed food advertisement bans, and school regulations. The policy was implemented in 3 phases from 2016 to 2019 and the primary objective was to improve children's food environments. This study's objective was to assess changes in child and adolescent intake of key nutrients of concern (total sugars, saturated fats, and sodium) at school after the initial implementation of Chile's Law of Food Labeling and Advertisement. Methods Longitudinal study of 349 children from the Food Environment Chilean Cohort (FECHIC) and 294 adolescents from the Growth and Obesity Cohort Study (GOCS). Data were from single 24-hour dietary recalls collected from 2016 to 2019. Fixed-effects models stratified by school, home, and other locations compared nutrient consumption in each year to consumption at the pre-policy 2016 baseline. Nutrient intakes are expressed as percent of total energy. Results Compared to 2016 (pre-policy), total sugars consumed by children at school decreased 4.5 [-8.0, -0.9] percentage points (pp) and 11.8 [-15.4, -8.3] pp in 2018 and 2019 respectively. In 2019, children's saturated fats and sodium intake at school also decreased (1.1 [-1.9, -0.2] pp and 10.3 [-18.1, -2.5] mg/100 kcal respectively). Likewise, in adolescents, total sugars and saturated fats consumed at school decreased in 2018 (5.3 [-8.4, -2.2] pp and 1.5 [-2.7, -0.3] pp respectively). However, consumption of key nutrients of concern at other locations increased after implementation of the policy. Conclusions After initial implementation of Chile's Labeling Law, intake of most key nutrients of concern significantly declined at school. However, we found evidence of compensatory behavior in out-of-school settings. Further research is needed to evaluate what other actions are needed to impact overall diets in the long term both at schools and out of school.